Determination of Glutamate Dehydrogenase in Ascaridia Galli, Parasitizing Gallus Gallus Domesticus - Govind H. Balde, Sanjay S. Nanware and (Recent Research in Science and Technology, 2011)
Glutamate formed by the action of the transaminases and may undergo rapid oxidative deamination catalysed by the pyridine linked glutamate dehydrogenase. Biosynthesis of GDH takes place on microsomes and then it is transported, possibly by phospholipids in to mitochondria. Some literature citations are available with the study of GDH activity. Pollak and Fairbairn, (1955), Perez-Gimenez, et al, (1967), Langer, (1972) and Rhodes and Ferguson, (1973). The present investigation carried out the study of GDH activity in nematode parasite Ascaridia galli (Schrank, 1788), Freeborn, 1923 of naturally infected Gallus gallus domesticus. In this studies estimated data represent respectively in male and female is 1.52 ± 0.25 and 2.11 ± 0.744 µmoles/hour/100 mg tissue, indicate that activity exceeds in females than males.